Evaluation of Nursing staff Performance in Cardiac Care Units at Teaching and Non Teaching Hospitals in Kirkuk City: A Comparative Study - Baiez, yas; Mohammed, widad (Iraqi National Journal of Nursing Specialties, 2015)
Objective: The descriptive study was used to evaluate nursing staff performance in cardiac care units at teachingand non teaching hospitals in kirkuk city: A comparative study.Methodology: A descriptive study was used to evaluate nursing staff performance in cardiac care units. The studywas conducted from December 29th, 2013 up to the 27th of Apr. 2014. A non-probability (purposive) sample of(44) nurses who work in cardiac care unit at Azady teaching Hospital and Kirkuk general Hospital was evaluated bya questionnaire which consisted of two parts; the first part is concerned with the demographic characteristics ofthe nurses and the second part concerned Observation check list for evaluation nursing staff Performance inCardiac Care. Validity of the observational check list performed through a panel of (02) experts and the reliability ofthe questionnaire is determined through the pilot study. Descriptive and inferential statistical used to analysis ofdata.Results: the study shows that (61.4%) of the samples age were (20-30) years old, (63.6%) were male. (68.2%) ofthem Graduate B.Sc. of Nursing. most of the samples has (1-5) Years of experience in Nursing. the results showsthat a high assessment of observational Check List are reported for the following domains: Maintenance respirationby adequate O2 supply, Decrease SVR (systematic vascular resistance), Monitor ABGs (Arterial blood gases)frequently. Also the study reveals that moderate assessments of observational Check List are reported for reamingdomains.Recommendations : Providing opportunity for nurses in cardiac care units to continuing updating their educationto maintain knowledge and skills.